COGNITIVE CHANGES AMONG OLDER ADULTS: WHAT KINDS OF SOCIAL ENGAGEMENT ACTIVITIES MATTER? - Chen, Y (Innov Aging, 2018)
The use-it-or-lost-it hypothesis on cognitive abilities suggests that one must continually practice cognitive ability or risk losing it. It makes intuitive sense but has found mixed evidence in cognitive aging research. The primary purposes of the present study are twofold: 1) to investigate the relationships between social engagement activities (i.e., cognitive and social activities) and cognitive functions (i.e., episodic memory, working memory, and processing speed) of older adults; and 2) to analyze what kinds of social engagement activities matter in changes of cognitive functioning of older adults during 2-year intervals. Data were drawn from two waves of the Population Study of Chinese Elderly in Chicago (PINE), which assessed 3,159 Chinese older adults between 2011–2013 for Wave 1 and 2013–2015 for wave 2. In addition to socio-demographic variables, participants completed measures of cognitive and social activities and multiple Cognitive tests (i.e., East Boston Memory Test, Digit Span Backwards, and Symbol Digit Modalities Test). Controlling for age, sex, marital status, education, income, years_in_US, and health status, it was found that both kinds of social engagement activities were positively associated with all three cognitive functions at Wave 1. However, only changes in cognitive activities significantly predicted changes in episodic memory between Wave 1 and Wave 2. Findings support the use-it-or-lose-it hypothesis of cognitive activities and are consistent with the recent findings of neurogenesis studies and the Synapse Project on cognitive training of older adults. Implications are discussed in terms of potential training and interventions to facilitate cognitive functioning among U.S. Chinese older adults.